Gauging trauma-informed pedagogy in higher education: a UK case study - Bitanihirwe, Byron; Imad, Mays (Frontiers in Education, 2023)
A vast body of evidence exists suggesting a negative association between traumatic experiences and mental health among primary and secondary school students.Vulnerable students that have experienced trauma or adverse childhood experiences are reported to be at an increased risk of academic, social, and emotional problems. In contrast to the clear evidence stemming from primary and secondary schools, there is a dearth of evidence examining links between traumatic experiences and student mental health in higher education, including in relation to the incorporation of trauma-related content in the classroom setting. Here we present recent findings from a study examining students' experiences of exposure to traumatic material in a UK university. Moreover, perceptions of trauma-informed pedagogy by educators teaching at the university level are also explored. Eight students from the University of Manchester and seven educators (teaching in the humanities and social sciences) underwent a one-on-one semi-structured interview. Analysis involved an inductive thematic approach. Four themes emerged from the analysis of the interview data: 1) inclusion and delivery of trauma-related content in higher education; 2) effects of trauma-related content on class attendance; 3) access to support systems for dealing with trauma-related content and 4) perceptions on traumainformed education. Implications of the study for future research and current teaching practice are discussed, along with recommendations for teaching sensitive material in general. Limitations of the study include issues related to sample size and demographics.Finally, we also provide a conceptual framework for educators in terms of traumainformed pedagogy which will serve as the foundation for a future concept paper.